Small-Group Learning in Science Perspective towards Classroom Engagement - Behera, Biswajit (INDIAN EDUCATIONAL REVIEW, 2022)
This paper contributes to the understanding of teacher trainees’ engagement during Problem-based Small Group Learning (SGL). Six participants were selected purposively, who filled informed consent and were affirmative in giving extra time for this experiment. The process of sharing and interaction during SGL was studied through a qualitative case study. The study components included the group, roles of participants, peer-group relations, encountered situations and the practice of sessions. Participant observation, focus group discussion and field notes were the measures for data collection. The researcher facilitated the group members during SGL in various possible ways such as observed group works, checked solutions, gave hints, clarified notations, asked and answered questions, pointed out errors and helped the group to work. The result revealed that, SGL was effective to promote socially accepted behaviours as well as cognitive behaviour. Classroom engagement consisting of behavioural engagement was demonstrated through the participation and effort of learners in activities. Consequently, classroom engagement was enhanced through pedagogical method and classroom environment.